IYQ 2025: Homoeopathy within Scope of Quantum Science & its Applications (Advancements in Homeopathic Research, 2025)
The International Year of Quantum Science and  Technology (IYQ) 2025 is a global initiative  celebrating 100 years since the development of  quantum mechanics1. This year-long event aims to  raise awareness about the importance of quantum  science and its applications2.  There is optimism about huge potential for quantum  computing in areas such as chemistry, biochemistry  and materials science — significantly advancing fields  such as healthcare and manufacturing, especially  when used to refine and improve artificial intelligence  models3. Quantum science and technology have the  potential to revolutionize various fields, including  medicine.  Homeopathy is well represented in Indian landscape  of public health, being a close second among the  AYUSH (Ayurveda, Yoga and Naturopathy, Unani,  Siddha and Homeopathy) services. India offers  a range of medical treatment modalities to its  population in a cafeteria approach. Ministry of Ayush  aims at providing its people with wider access to  homeopathy. Homeopathy wellness centres comprise  31% of the total for AYUSH. Seven out of 10 diseases  recognised as a national health burden are in the  category of most commonly reported diseases at the  homeopathy wellness centres4.
Keywords: International; Year; Quantum; Science; global initiative; quantum; mechanics1